GPS based vehicle tracking system - Zohari, Mohd Hakimi; Mohd Nazri, Mohd Fiqri (2021)
The research is about creating a system for tracking vehicle. Objective of the research is to design and develop a GPS based Vehicle Tracking System in order to display location of vehicle on Google Maps. This system used Arduino MEGA as a microcontroller and it will be used as the main processing unit. Next, Ublox NEO-6m GPS module is used to routing the coordinate while SIM 900A GSM module is used to connecting with the user. The product was successfully run at outdoor and having some problem at indoor due to GPS module cannot extract the accurate coordinate when there is a roof or obstructer that block the direct signal connection between the GPS and satellite. For the next improvement, the researcher can use the high quality of GPS module to connect with satellite. An example, GPS NEO-6P module where it can collect data more accurate and stay connect to the satellite.